Muscle Adaptations to High-Load Training and Very Low-Load Training With and Without Blood Flow Restriction - Jessee, Matthew B.; Buckner, Samuel L.; Mouser, J. Grant; Mattocks, Kevin T.; Dankel, Scott J.; Abe, Takashi; Bell, Zachary W.; Bentley, John P.; Loenneke, Jeremy P. (Frontiers in Physiology, 2018)
An inability to lift loads great enough to disrupt muscular blood flow may impair the ability to fatigue muscles, compromising the hypertrophic response. It remains unknown what level of blood flow restriction (BFR) pressure, if any, is necessary to reach failure at very low-loads (i.e., 15%1RM). The purpose of this study was to investigate muscular adaptations following resistance training with a very low-load alone (15/0), with moderate BFR (15/40), or with high BFR (15/80), and compare them to traditional high-load (70/0) resistance training. Using a within/between subject design, healthy young participants (n=40) performed four sets of unilateral knee extension to failure (up to 90 repetitions/set), twice per week for eight weeks. Data presented as mean change (95% CI). There was a condition by time interaction for 1RM (p<.001), which increased for 70/0 [3.15 (2.04,4.25) kg] only. A condition by time interaction (p=.028) revealed greater changes in endurance for 15/80 [6 (4,8) repetitions] compared to 15/0 [4 (2,6) repetitions] and 70/0 [4 (2,5) repetitions]. There was a main effect of time for isometric MVC [change = 10.51 (3.87,17.16) Nm, p=.002] and isokinetic MVC at 180/second [change = 8.61 (5.54,11.68) Nm, p<.001], however there was no change in isokinetic MVC at 60/second [2.45 (-1.84,6.74) Nm, p=.261]. Anterior and lateral muscle thickness was assessed at 30, 40, 50, and 60% of the upper leg. There was no condition by time interaction for muscle thickness sites (all p≥.313). There was a main effect of time for all sites, with increases over time (all p<.001). With the exception of the 30% lateral site (p=.059) there was also a main effect of condition (all p<.001). Generally, 70/0 was greater. Average weekly volume increased for all conditions across the eight weeks, and was greatest for 70/0 followed by 15/0, 15/40, then 15/80. With the exception of 1RM, changes in strength and muscle size are similar regardless of load or restriction. The workload required to elicit these changes lowered with increased BFR pressure. These findings may be pertinent to rehabilitative settings, future research, and program design.